STUDYING COASTAL COMMUNITIES IN THE BANGKA BELITUNG ISLANDS PROVINCE FROM A SOCIOECONOMIC AND CULTURAL PERSPECTIVE - Bidayani, Endang; Wahidin, La Ode; Priyambada, Agung; Umroh, Umroh; Akhriyanti, Irma; Syari, Indra Ambalika; Gustomi, Andi; Arizona, Mohammad Oka; Batubara, Geothani Harapan Putera; Pamungkas, Aditya; Astrida, Nikki; Bayyan, Muhammad Miftahul; et al. (Jurnal Perikanan Unram, 2025)
The coastal area in the Bangka Belitung Islands Province has high mangrove biodiversity with an area of 67,386 Ha. The purpose of the study was to examine the social, economic, and cultural aspects of the coastal communities of the Bangka Belitung Islands Province. The research method was a survey. Data collection consisted of primary and secondary data. Primary data were obtained directly from in-depth interviews with 129 informants from 13 coastal villages determined purposively on Bangka Island and Belitung Island. Primary data collection used questionnaires, observation and documentation. Secondary data were obtained from the village office and related agencies. The results of the study, the social conditions of the community include PLN electricity sources, the main source of water for the community is well water, the transportation route is land transportation, public facilities include mosques, prayer rooms, soccer fields, volleyball courts, village libraries and the main signal towers are Telkomsel and Indosat. The religion practiced by the majority of the community is Islam. The types of work of the coastal village community recorded consist of educators, medical personnel, midwives, traders, fishermen, self-employed, unemployed and others. Economic conditions include district/city GRDP, namely the highest GRDP value in Bangka Regency in 2023 of IDR 11,756,196 million and the lowest in East Belitung Regency of IDR 6,211,049 million. Local wisdom or culture in the Bangka Belitung Islands Province includes: Maulid, Ruahan, Isra miraj, nisfu syaban, Satu Muharram, Rebo kasan, Peh Cun and Perang Ketupat. Public perception of the existence of mangrove forests and unconventional mining in coastal areas is in the Good category, while community participation in mangrove rehabilitation/protection and coastal community preferences related to the economy that they want to develop are in the Medium category. The economic preferences that they want to develop are fish, shrimp and crab cultivation, fish processing such as kemplang and shrimp paste, nipah crafts and mangrove tourism.